PEMBUATAN SEDIAAN MINUMAN SERBUK RUMPUT LAUT (Eucheuma cottonii) DAN UJI CEMARAN Salmonella sp. - Hurera Citra Nur Atami; Sri Wahyuni, Yuyun; Imansyah, Maulana Zulkarnain (Jurnal Kesehatan Yamasi Makassar, 2023)
This study aims to determine whether there is contamination of Salmonella typhi. The test material in the form of seaweed was made into instant powder drink preparations by heating/crystallization method. Then the Salmonella typhi contamination test was carried out. The test results showed that there was a change in color/turbidity which showed a positive coliform group, but a follow-up test with SSA showed negative results. So it was concluded that the preparation of seaweed powder drink did not contain Salmonella typhi.